Orogenic Collapse and Stress Adjustments Revealed by an Intense Seismic Swarm Following the 2015 Gorkha Earthquake in Nepal - Adhikari, Lok Bijaya; Bollinger, Laurent; Vergne, Jérôme; Lambotte, Sophie; Chanard, Kristel; Laporte, Marine; Li, Lily; Koirala, Bharat P.; Bhattarai, Mukunda; Timsina, Chintan; Bishwokarma, Nabina; Wendling-Vazquez, Nicolas; et al. (Frontiers in Earth Science, 2021)
The 25 April 2015 Mw 7.9 Gorkha earthquake in Nepal was characterized by a peak slip of several meters and persisting aftershocks. We report here that, in addition, a dense seismic swarm initiated abruptly in August 2017 at the western edge of the afterslip region, below the high Himalchuli-Manaslu range culminating at 8156 m, a region seismically inactive during the past 35 years. Over 6500 events were recorded by the Nepal National Seismological Network with local magnitude ranging between 1.8 to 3.7 until November 2017. This swarm was reactivated between April and July 2018, with about 10 times less events than in 2017, and in 2019 with only sporadic events. The relocation of swarm earthquakes using proximal temporary stations ascertains a shallow depth of hypocenters between the surface and 20 km depth in the High Himalayan Crystalline slab. This swarm reveals an intriguing localized interplay between orogenic collapse and stress adjustments, involving possibly CO2-rich fluid migration, more likely post-seismic slip and seasonal enhancements.